Influence of process parameters on the properties of pulsed laser deposited CuIn0.7Ga0.3Se2 thin films. (1st November 2018) - Nicolaou, Christiana; Zacharia, Anna; Itskos, Grigorios; Giapintzakis, John
Graphical abstract: Highlights: Threshold value of laser fluence for obtaining stoichiometric films is 0.8 J/cm 2 . Threshold value of background pressure for stoichiometric films is 0.01 mbar. The electrical properties of the films are mostly affected by the Cu2−x Se phase. High absorption coefficient of ∼2–3 ∗ 10 4  cm −1 for CuIn0.7 Ga0.3 Se2 films. Long photoluminescence lifetime of ∼50 ns for the film grown at 500 °C. Abstract: This work reports on the influence of pulsed laser deposition growth parameters on the properties of CuIn0.7 Ga0.3 Se2 thin films. Polycrystalline CuIn0.7 Ga0.3 Se2 thin films were grown on soda-lime glass substrates under various growth conditions. Morphological, compositional, structural, electrical and optical properties of CuIn0.7 Ga0.3 Se2 thin films were investigated as a function of laser fluence, background gas and substrate temperature. A threshold of laser fluence, 0.8 J/cm 2, and background pressure, 0.01 mbar, determined through a systematic parametric investigation, for obtaining stoichiometric films. A minor secondary phase of Cu2−x Se was observed by X-ray diffraction, and found to gradually diminish with increasing deposition temperature. The film grown at 500 °C shows the purest CuIn0.7 Ga0.3 Se2 chalcopyrite phase. The electrical properties of the films, i.e., dark resistivity, carrier concentration and mobility, are shown to be mostly affected by the Cu2−x Se phase and the crystal quality of the films. All films exhibit high absorption coefficients of ∼2–3 ∗ 10 4  cm −1 in the vicinity of the band-edge; a blue shift of the energy gap with deposition temperature is attributed to the relaxation of the lattice strain, as corroborated by the respective shift of (1 1 2) peak of the XRD patterns. The monotonic increase of the photoluminescence intensity accompanied by the concomitant decrease of the emission linewidth and Stokes shift indicate an improvement in the material quality and uniformity as deposition temperature increases in accordance with the structural and electrical measurement findings. Long PL lifetime of ∼50 ns is measured in the band-edge region for the film grown at 500 °C, suggestive of a single phase material with low defect density. Our results overall indicate that high-quality, stoichiometric CuIn0.7 Ga0.3 Se2 thin films can be obtained using pulsed laser deposition, a rapid single-step growth method that eliminates the need for post-selenization.